1991
DOI: 10.2307/3283093
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma danilewskyi in Carassius auratus: The Nature of Protective Immunity in Recovered Goldfish

Abstract: Trypanosoma danilewskyi is pathogenic to goldfish, Carassius auratus; the number that survived an infection was related to the size of inoculum, i.e., the mortality was low when the inoculum was small. Most fish that had prior exposure(s) to the parasite survived subsequent homologous challenge(s) and were protected for at least 89 days. The immunity was nonsterile as low numbers of parasites were detected in the blood of some recovered fish. Intraperitoneal injection of corticosteroid in recovered fish signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Acquired protective immunity in fish has previously been confirmed against several freshwater species of protozoa, including I. multifiliis (Hines & Spira, 1974) and the haemoflagellates, Cryptobia salmositica (Wehnert & Woo, 1981;Jones & Woo, 1987) and Trypanosoma danilewskyi (Woo, 1981;Islam & Woo, 1991). It is probable that fish respond similarly to many other species of protozoa including Ichthyobodo necator (Tavolga & Nigrelli, 1947;Robertson, 1979), and the marine parasite Amyloodinium occelatum (Lawler, 1980;Paperna, 1980).…”
Section: Discussionmentioning
confidence: 89%
“…Acquired protective immunity in fish has previously been confirmed against several freshwater species of protozoa, including I. multifiliis (Hines & Spira, 1974) and the haemoflagellates, Cryptobia salmositica (Wehnert & Woo, 1981;Jones & Woo, 1987) and Trypanosoma danilewskyi (Woo, 1981;Islam & Woo, 1991). It is probable that fish respond similarly to many other species of protozoa including Ichthyobodo necator (Tavolga & Nigrelli, 1947;Robertson, 1979), and the marine parasite Amyloodinium occelatum (Lawler, 1980;Paperna, 1980).…”
Section: Discussionmentioning
confidence: 89%
“…Since T. carassii is an extracellular parasite, the induction of IFN-g (a Th1 cytokine) may cause reduction in Th2 type cytokine production and affect host's humoral immune responses, an immune evasion mechanism similar to that shown for S. mansoni (24). It is well established that anti-parasite antibody responses are essential for T. carassii clearance and maintenance of long lasting resistance to re-infection [3,34,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, passive transfer studies have shown that immunity to re‐infection can be transferred to naïve goldfish by injecting them with plasma or purified IgM from a recovered host (Woo 1981; Lom & Dykova 1992; Overath, Haag, Mameza & Lischke 1999). Resistance to re‐infection was shown to be long‐lasting (as long as 365 days) and is believed to be due to the sequestration of parasites in the internal organs resulting in constant priming of the immune system (Woo 1981; Islam & Woo 1991). Recently, protective antibodies were shown to be induced in naïve goldfish after immunization with parasite excretory/secretory products (Bienek, Plouffe, Wiegertjes & Belosevic 2002).…”
Section: Introductionmentioning
confidence: 99%